2022
DOI: 10.29173/cjnser564
|View full text |Cite
|
Sign up to set email alerts
|

On the Front Lines: Nonprofits in the Homeless-serving Sector During the COVID-19 Pandemic

Abstract: This article examines the experiences of the nonprofit, homeless-serving sector during the first wave of the COVID-19 pandemic. Qualitative interviews were conducted with staff and volunteers from frontline organizations in the two largest communities in Nova Scotia, Canada. Participants reported much strain on their organizations' human resources, but also the ability to adjust service delivery mechanisms quickly in order to continue offering supports. Most reported greater in-kind contributions from business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They can encourage collaboration between NGOs and the government to prepare effectively for disasters and ensure communication to groups is clear, so the effects of the disaster are contained (Karabanow et al 2023). Social work practitioners can ensure agencies meet immediate needs and support recovery work to restore communities' stability by engaging collaboratively (Leviten-Reid et al 2022). Furthermore, social workers are called upon to build strength with individuals and their communities to recover after extreme events.…”
Section: Gsw Practice and Building Resilience In Disaster Settingsmentioning
confidence: 99%
“…They can encourage collaboration between NGOs and the government to prepare effectively for disasters and ensure communication to groups is clear, so the effects of the disaster are contained (Karabanow et al 2023). Social work practitioners can ensure agencies meet immediate needs and support recovery work to restore communities' stability by engaging collaboratively (Leviten-Reid et al 2022). Furthermore, social workers are called upon to build strength with individuals and their communities to recover after extreme events.…”
Section: Gsw Practice and Building Resilience In Disaster Settingsmentioning
confidence: 99%
“…At the same time, there have been reports of various impacts on nonprofits regarding financing (Hutton et al, 2021;Jeong & Kim, 2021;Luong et al, 2022;Meyer et al, 2021;Plaček et al, 2022;Shi, 2022). Other difficulties were related to volunteering due to lockdowns and the virus itself (Biddle & Gray, 2020;Leviten-Reid et al, 2022;Shi, 2022) or a lack of nonprofit staff (Leviten-Reid et al, 2022;Santos & Laureano;). Among other consequences, studies showed reducing the quantity and quality of nonprofits services (Searing et al, 2021), disrupting the practices of nonprofits (Meyer et al, 2021) and also difficulties regarding teamwork due to limited possibilities to meet face to face (Shi, 2022), increased the stress of nonprofit workers (Leviten-Reid et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Other difficulties were related to volunteering due to lockdowns and the virus itself (Biddle & Gray, 2020;Leviten-Reid et al, 2022;Shi, 2022) or a lack of nonprofit staff (Leviten-Reid et al, 2022;Santos & Laureano;). Among other consequences, studies showed reducing the quantity and quality of nonprofits services (Searing et al, 2021), disrupting the practices of nonprofits (Meyer et al, 2021) and also difficulties regarding teamwork due to limited possibilities to meet face to face (Shi, 2022), increased the stress of nonprofit workers (Leviten-Reid et al, 2022). Aside from being impacted by the pandemic, nonprofits and volunteering were also participating in dealing with the pandemic (Azevedo et al, 2022;Biddle & Gray, 2020;Jeong & Kim, 2021;Kuenzi et al, 2021;Meyer et al, 2021;Wang & Cheng, 2021).…”
Section: Introductionmentioning
confidence: 99%